Strategi Orang Tua Dalam Pendampingan Belajar Anak Selama Pandemi Covid-19 - Shokhib Rahmania; Retno Wijayanti; Shiddiq Luqman Hakim (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
Parental assistance often influences the role of children to maintain good habits. Assistance that is not optimal allows children to freely do bad things to themselves and others. This study aims to determine how parents can assist their children in learning during the Covid-19 pandemic. This research uses descriptive qualitative method. The method for data collection is interviews. The research sample consisted of parents of students at SD Islam Terpadu Taqiyya Rosyida Surakarta. In selecting the subject, the researcher took 3-5 respondents who were taken randomly. The results of the study identified that there is a lack of parents who do not pay much attention to their children's learning assistance by leaving it to their grandparents, uncle or aunt, or to their wives only. How to accompany learning with the method of games, storytelling, and assignments as well as supervision while learning.